An HPLC-PAD method to analyse flavonoid glycosides and styrylpyrones from Cryptocarya species (Lauraceae) - Nehme, C. J.; Bastos, W. L.; de Araujo, A. J.; Cavalheiro, Alberto José [UNESP] (Wiley-Blackwell, 2005)
An HPLC-PAD method has been developed in order to evaluate simultaneously the main secondary metabolites, flavonoid glycosides and styrylpyrones, of leaves of Cryptocarya moschata. The sample preparation, consisting of extraction, liquid-liquid extraction and centrifugation, requires minimum sample manipulation but produces high yields with reproducibility, selectivity and simplicity. HPLC on a C, column presents each class of metabolites grouped and with good resolution of the main compounds. The experimental conditions can be used to study inter- and intra-specific variability of secondary metabolites in Cryptocarya spp. Copyright (c) 2005 John Wiley A Sons, Ltd.
Keywords: HPLC-PAD; retention index; flavonoid glycosides; styrylpyrones; Cryptocarya moschata; Lauraceae